Penentuan Distribusi Suhu pada Pelat Logam dengan Cara Menyelesaikan Persamaan Diferensial Eliptik Menggunakan Microsoft Excel - Lukman Samatowa; Septiana Kurniasari; Muhammad Yunus; Relita Damopolii (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to visualize the temperature distribution on metal plates by solving elliptic differential equations using the help of the Microsoft Excel program. Many physics problems have limited analytic solutions so a numerical solution is needed. One of them is about the temperature distribution on a homogeneous metal plate in a steady-state conditionThe equation of heat flow in steady-state conditions is an elliptic partial differential equation (PDE). By solving this equation, we will have a numerical model of the plate that can be a mesh with a certain temperature point. Each point has been known to calculate the temperature value. The temperature value influenced. The Temperature value influenced borders on the plate and the presence of heat generation. The edge of the plate can be a constant temperature, a convection zone with the outside air, or an isolated edge. This model is then processed using Microsoft Excel with the iteration calculation until the temperature distribution value is obtained. The results obtained a graphical visualization of temperature distribution on the plate.